The bullet caucus: from the national congress to social media - Benetti, Pedro Rolo; Alvarez, Marcos César (Revista Videre, 2021)
This paper discusses the discourses of congresspeople elected in 2018 as part of the so-called bullet caucus. To achieve this goal, we first explore the conditions that allowed this group to rise. While elections belong to the world of institutional politics, a number of social trends, both in Brazil and internationally, informed the creation of a distinctive identity by those congresspeople. Discourses attacking human rights and that have circulated in Brazil since the last democratic transition deserve special attention. Following this initial contextualization, we then discuss the arguments these congresspeople mobilized on social media during the 2018 election campaign, seeking to understand how they refer to issues such as violence, conflict, and human rights.